Mixed Adenoneuroendocrine Carcinoma Causing Colonic Intussusception - Marina Morais; André Costa Pinho; Ana Marques; Joanne Lopes; Alexandre Duarte; Pedro Correia da Silva; José Manuel Lopes; J. Costa Maia (Case Reports in Surgery)
Colonic intussusception is a rare cause of intestinal obstruction in adults and is caused by a malignant lesion in about 70% of cases. Early diagnosis and treatment are essential. We present a 64-year-old male patient with right colonic intussusception caused by a mixed adenoneuroendocrine carcinoma (MANEC), presenting as a giant pedunculated polyp (54 mm of largest diameter). The patient underwent right colectomy with primary anastomosis and adjuvant chemotherapy. The diagnosis of intussusception of the colon in adults is difficult because of its rarity and nonspecific clinical presentation. In this case, the cause was a rare histological type malignant tumor (MANEC).